Nitrous oxide fluxes and their correlations with physical and chemical soil properties - Corrêa, Rubia Santos; Madari, Beáta Emöke; Carvalho, Glaucilene Duarte; Costa, Adriana Rodolfo; Pereira, Ana Cláudia Castro; Medeiros, João Carlos (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the dynamics of nitrous oxide (N2O) fluxes in a soil under pasture, in an integrated crop-livestock system, and in native cerrado as a reference, besides identifying the physical and chemical soil properties that affect the fluxes. The study was conducted at Fazenda Capivara of Embrapa Arroz e Feijão, in the state of Goiás, Brazil, between February 5 and September 30, 2013. Gas sampling was performed using manual static chambers. The soil under pasture showed the highest N2O fluxes with average of 14.12 ng m-2 s-1. This area also showed greater water-filled pore space (WFPS), which, associated with soil temperature and nitrate content in the soil affected the production of N2O. In the rainy season, fluxes showed positive correlation with soil WFPS, and, in the dry season, they were correlated with soil contents of ammonium and nitrate. The total N2O emission in the pasture area was 1,644.19 g ha-1. In native cerrado, there was no soil-N2O emission to the atmosphere.